1999
DOI: 10.1007/s002449900449
|View full text |Cite
|
Sign up to set email alerts
|

Primary DNA Damage But Not Mutagenicity Correlates with Ciprofloxacin Concentrations in German Hospital Wastewaters

Abstract: Recently, we showed for the wastewater of a large Swiss university hospital that primary DNA damage, assessed by a bacterial SOS repair assay (umuC test), could be largely assigned to a specific class of antibiotics, the fluoroquinolones (FQs) (Hartmann et al. [1998] Environ Toxicol Chem 17:377-382). In an attempt to confirm the significance of FQs for the bacterial DNA damaging effects in native hospital wastewaters, 25 samples from five German clinics were screened in this study by the umuC test. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(81 citation statements)
references
References 16 publications
3
75
0
3
Order By: Relevance
“…The results of the literature also showed the low sensitivity of the mammalian MN test in comparison to the SOS chromotest or the UmuC test, which revealed the positive effect of ciprofloxacin at 0.7 mg/L (Hartmann et al, 1999). Topoisomerases-II inhibitors like CIP and ofloxacin are very strong genotoxicants in Escherichia coli PQ 37 (SOS chromotest) and highly mutagenic in Salmonella typhimurium TA 102 (Ames test) in absence of exogenous metabolizing system (Mersch-Sundermann et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the literature also showed the low sensitivity of the mammalian MN test in comparison to the SOS chromotest or the UmuC test, which revealed the positive effect of ciprofloxacin at 0.7 mg/L (Hartmann et al, 1999). Topoisomerases-II inhibitors like CIP and ofloxacin are very strong genotoxicants in Escherichia coli PQ 37 (SOS chromotest) and highly mutagenic in Salmonella typhimurium TA 102 (Ames test) in absence of exogenous metabolizing system (Mersch-Sundermann et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Ciprofloxacin was found in concentration ranging from 0.7 to 124.5 mg/L in hospital effluents and was assumed to be the main source of genotoxic effects measured with the UmuC test in these effluents (Hartmann et al, 1999). Fluoroquinolones have been reported to induce unscheduled DNA synthesis, DNA strand breakage, chromosome damage and micronuclei formation (Mc Queen et al, 1991;Holden et al, 1989;Bredberg et al, 1991;Ciaravinco et al, 1993;Curry et al, 1996;Gibson et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The environmental concentrations of quinolones are up to 120 ng/L, 500 ng/L and 125 μg/L in surface waters, secondary wastewater effluents of sewage treatment plants and untreated hospital wastewater (Golet et al, 2002(Golet et al, , 2003Hartmann et al, 1998Hartmann et al, , 1999Kolpin et al, 2002;Miao et al, 2004;Renew and Huang, 2004). From the current study, it is reasonable to infer that quinolones, which at residual level of environment, cannot lead to short-term acute toxicity to photobacterium V. fischeri.…”
Section: Toxicity Of Quinolones In Aquatic Environmentmentioning
confidence: 73%
“…We theorized that the [ Here we report the effects of ciprofloxacin, one of the most prescribed of the quinolone antibiotics in the world [7], an antibiotic that inhibits DNA production in susceptible microbes, on planktonic bacteria in river and wetland waters as measured by the incorporation of [ 3 H] thymidine into DNA. Ciprofloxacin has been detected in the environment and wastewater from ηg to low µg•L −1 [5] while concentration in hospital effluent has been measured at up to 124.5 µg•L −1 [8] and a total of eight quinolones, including ciprofloxacin, at 9 mg•kg −1 (dry weight) in sewage sludge [9]. Although the concentration of antibiotics in open waters is low, it should not be assumed that the effects on bacteria and selection pressure for resistant strains are negligible as it has been found that a constant applied dosage at a tenth of MIC has a strong influence on selecting for resistant microbes [10].…”
Section: Introductionmentioning
confidence: 99%